Occurrence of Trichodina ahmedi Asmat, 2005 and Trichodina heterodentata Duncan, 1977 in the freshwater major carp Gibelion catla (Hamilton, 1822) from Hakaluki haor, Bangladesh (Bangladesh Journal of Zoology, 2026)
A systematic assessment of trichodinid ciliates of the genus Trichodina Ehrenberg, 1830, was conducted in Hakaluki Haor, Bangladesh. This survey reported two species, Trichodina ahmedi Asmat, 2005 (prevalence 7.8%) and Trichodina heterodentata Duncan, 1977 (prevalence 5.2%), from the gills of Gibelion catla (Hamilton, 1822). This provides the first evidence of these species in Hakaluki Haor, adding important insights into the diversity and geographical range of trichodinid parasites in Bangladesh. Detailed morphological features are provided using Klein’s (1958) silver nitrate impregnation method, including photomicrographs. These records also afford new host and locality information for these ciliates.Bangladesh J. Zool. 53(3): 255-265, 2025